2016
DOI: 10.1108/tpm-12-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Mindful infrastructure as an enabler of innovation resilience behaviour in innovation teams

Abstract: Purpose This paper aims to investigate the principles of high reliability organisations (HROs), present in safety and crisis teams, as applied to innovation teams. Safety and crisis teams cannot fail, as failure leads to disaster and casualties. Innovation teams cannot fail either, as this harms the organisations’ competitiveness and effectiveness. Do HRO principles, rooted in mindful infrastructure, enable innovation resilience behaviour (IRB)? Design/methodology/approach A study of 18 innovation projects p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…There is much less empirical research into the interaction of leadership and resilience at the team and organizational levels. There is some support for the claim that leadership enables team level resilience (Oeij et al, 2016). However, studies range widely as to which specific leadership behaviors impact team level resilience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is much less empirical research into the interaction of leadership and resilience at the team and organizational levels. There is some support for the claim that leadership enables team level resilience (Oeij et al, 2016). However, studies range widely as to which specific leadership behaviors impact team level resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Team resilience is the least developed level of resilience research (Raetze et al, 2019). Oeij et al (2016) used a short version of the Five Audits of Resilient Performance measure to evaluate team resilience among 18 innovation teams. They found that “resilience appears most often when team voice, team learning, and all four leadership styles (compete, create, control, and collaborate) are present” (Oeij et al, 2016, p. 344).…”
Section: Current Streams Of Research At the Intersection Of Resilienc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the observation remains relevant that the bivariate association of all mindful infrastructure variables with team IRB is present in the data set. The stipulated analyses are carried out applying qualitative comparative analysis and findings are reported elsewhere (Oeij et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…All of these activities need to be managed effectively and efficiently through Innovation Management. (Oeij, Dhondt, & Gaspersz, 2016) suggests that Innovation management is a management discipline related to managing innovation in processes, products and services, organizations, to customers and markets. Innovation management can be used to develop innovation processes, products and services, organizations, and markets and customers.…”
Section: Business Model Innovationmentioning
confidence: 99%